3sinx = 2cosx

let us square both sides:

==> 9sin^2 x = 4cos^2 x..........(1)

We kow that :

sin^2 x + cos^2 x = 1

==> sin^2 x = 1 - cos^2 x

==> Substitute in (1):

==> 9(1-cos^2 x) = 4cos^2 x

==: 9 - 9cos^2 x = 4cos^2 x

Combine like terms:

==> 9- 13cos^2 x = 0

==> 13cos^2 x = 9

==: cos^2 x = 9/13

==> cosx = +-3/sqrt13

**==> x= arccos(3/sqrt13) + 2npi **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now